Thick as thieves [compact disc, unabridged] - Brown, Sandra, 1948- (Hachette Audio, 2020)
Twenty years ago, four seemingly random individuals pulled the ultimate heist and almost walked away with half a million dollars. But by daybreak, one of them was in the hospital, one was in jail, one was dead, and one got away with it. Arden Maxwell, the daughter of the man who disappeared all those years ago presumably with the money after murdering his accomplice, has never reconciled with her father's abandonment. She decides to return to her family home and finally get answers to the many questions that torment her. Little does she know, two of her father's co-conspirators, a war hero and a corrupt district attorney, are watching her every move. Although the two are bound to silence because of the crime they committed together, each has spent years waiting and hoping that the other will make a fatal misstep. But the arrival of their elusive accomplice's daughter, Arden, who may know more about the missing money than she's telling, sets them both on red alert.